Neuromodulators and Therapeutic Targets in Neuropathic Pain: From Molecules to Man - Bermejo, P. E.; Anciones, B. (CNS & Neurological Disorders - Drug Targets, 2009)
Neuropathic pain is a phenomenon characterized by a high population prevalence by possessing several etiologies. In contrast to nociceptive pain, painful signals in neuropathic pain are originated in the nervous system, present poor responses to conventional treatments and may worsen the quality of life. Antiepileptic drugs are increasingly used for different purposes including migraine, neuropathic pain, tremor or psychiatric disorders and they have started to be called neuromodulators. These drugs may act on very different targets such as sodium, potassium or calcium channels, purinergic, GABAergic, glutamatergic or vanilloid receptors and different cytokines including IL-6 or TNF, each if which may be important in managing some aspects of neuropathic pain. Antiepileptic drugs have demonstrated effectiveness in the treatment of this pathology, and owing to the important development of these drugs in the last years, they may become a very effective tool. On the other hand, the increasing knowledge of the pathophysiology of nociception is leading to new channels and receptors as potential targets for treatment. In this paper we try to review the different potential therapeutic targets and role of antiepileptic drugs in the treatment of this pathology.
Keywords: neuromodulator